Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5897/ajfs2013.1124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and hypolipidaemic effects of fermented Parkia biglobosa (Jacq) seeds in tyloxapol-induced hyperlipidaemic rats

Abstract: Globally, fermented foods form an intricate part of the staple diet of people. This study investigated the hypolipidaemic potential of fermented seeds of Parkia biglobosa (African locust bean/iru), a popular condiment by supplementing (20% w/w) in animal feed. Animals (n=5) in six treatment groups received; standard rat diet (control); iru-supplemented feed; standard rat feed with tyloxapol administered at the end of the experimental period (tyloxapol control); iru supplemented feed and triton at the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…This reduction is even lower than the reduction reported by the standard drug, statin. This result agrees with Ayo-Lawal et al (2014) who reported a decrease in the cholesterol level of the rats fed with fermented P. biglobosa seed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This reduction is even lower than the reduction reported by the standard drug, statin. This result agrees with Ayo-Lawal et al (2014) who reported a decrease in the cholesterol level of the rats fed with fermented P. biglobosa seed.…”
Section: Discussionsupporting
confidence: 93%
“…The observed increase in HDL for all treated groups is an indication of how effective the treatment has proven. This observed increase in HDL level in rats agrees with reports of Laleye et al (2016) and Ayo-Lawal et al (2014). Liong and Shah (2005) reported that high levels of HDL in animal and human blood protect against heart attack.…”
Section: Discussionsupporting
confidence: 92%
“…The condiment was effective in mitigating increased TC concentration, even better than at both concentration of the reference drug used in the study. Fermented Parkia biglobosa seeds showed similar observation when fed to tyloxapol-induced hyperlidaemic rats (Ayo-Lawal et al, 2014). The result of this study further showed that the condiment caused a significant (P < 0.05) increase in the plasma level of HDL-C, which is described as 'good cholesterol' (Agbedana, 1999).…”
Section: Discussionsupporting
confidence: 55%
“…These compounds promote vasorelaxation [ 182 ] by modulating nitric oxide availability [ 183 ] and inhibiting angiotensin-converting enzyme (ACE) [ 184 ], in addition to a reduction in oxidative stress [ 185 ], leading to blood pressure-lowering effects of the plant extract. The fermented seeds also decrease plasma triglyceride and cholesterol levels in Tyloxapol-induced hyperlipidemic rats [ 186 ], and platelet aggregation [ 187 ].…”
Section: Pharmacological Activities Of Parkia Smentioning
confidence: 99%